Male breast cancer: a Singapore perspective. Issue 6 (25th April 2022) - Lim, Joshua S. H.; Sim, Yirong; Ngeow, Joanne; Yuen, Jeanette; Tan, Veronique K. M.; Tan, Benita Kiat Tee; Yong, Wei‐Sean; Wong, Chow Yin; Lim, Sue Zann; Hamzah, Julie Liana B.; Tan, Si Ying; Wong, Fuh Yong; et al.
Abstract: Introduction: Male breast cancer (MBC) is rare, representing <1% of all breast cancers. Treatment recommendations have been extrapolated from trial data of female breast cancer patients. This study aims to report our institutional experience of MBC across a 20 year period, analyse the survival outcome and prognosis of this group against female breast cancer patients treated at the same centre. Methods: Clinical, histopathological, treatment and survival data of male and female breast cancer patients treated between Jan 1999 and July 2019 at Singapore General Hospital and National Cancer Centre Singapore were identified and analysed. Results: Fifty‐seven male patients were identified. The median age at diagnosis was 63 years. Majority had invasive ductal carcinoma (86%) and presented at an early disease stage: 70.2% presented as Tis/T1/T2 and 49.1% had no axillary nodal involvement. 84.2% had a simple mastectomy with either a sentinel lymph node biopsy or axillary clearance. The median follow up was 5.69 years for males and 5.83 years for females. The median survival was 11.86 years for males and 16.3 years for females. At 5 years, overall survival (OS) was 69.9% (52.3–82.1%) and disease free survival (DFS) was 62.9% (44.9–76.5%) for males compared with OS 83.8% (83.21–84.39%) and DFS 74.5% (73.91–75.09%) for females. Conclusion: MBC remains understudied. Our institutional data indicates that good long term survival in South‐East Asian patients can be achieved with treatment protocols that are similar to female breast cancer. More prospective studies are required. Abstract : Overall survival of MBC patients.